Tax avoidance in family firms: Evidence from large private firms. Issue 2 (August 2019) - Kovermann, Jost; Wendt, Martin
Abstract: Ownership structure plays an important role in firms' decisions on tax avoidance. Recently, the effect of family ownership on corporate tax avoidance has become an issue of increasing interest among scholars from both the fields of family business research and tax research; however, empirical findings have so far remained ambiguous. Based on a unique sample of 678 large private firms from Germany, we show that for unlisted large firms (i) family firms avoid more tax than non-family firms, (ii) tax avoidance increases with the percentage of family ownership, and (iii) tax avoidance is a function of the number of shareholders. We interpret our results as evidence that benefits from avoiding taxes outweigh the non-tax costs in the case of large private family firms in Germany. Furthermore, as the number of family shareholders increases, family firms satisfy increasing demand for dividends by avoiding taxes.